Hubungan Pengetahuan Obesitas dengan Rasio Lingkar Pinggang Panggul pada Ibu Rumah Tangga di Desa Pepe Krajan Kecamatan Tegowanu Kabupaten Grobogan - Isnaini -; Agus Sartono; Eny Winaryati (Jurnal Gizi, 2012)
Obesity is one of health problems in Indonesia. The trend of obesity is closely related to diet. Various factors play a role in the onset of obesity, but the most influence is the imbalance between food intake and physical activity. Obesity is condition where body’s weight is more than an ideal weight, which is affected by accumulation of fatty tissue or non fatty tissue including muscle, bone, fat and water. Factors affecting the occurrence of obesity are genetic, damage to one part of the brain, patterns of overeating, lack of movement / exercise, emotional impact, environmental, social economic and influence of drugs. This study used Waist Hip Circumference Ratio. Waist Hip Circumference Ratio can be used to detect excess fat on a person's body and accurately to detect the cause of Coronary Heart Disease (CHD) risk, some types of cancers, hypercholesterolemia, and hypertension. The purpose of this study was to determine the correlation between knowledge of obesity and housewives’ Waist Hip Circumference Ratio in Pepe Krajan village, Tegowanu district,Grobogan town.The results of the correlation test with 50 sample respondents showed that 56,0 % of respondents have high-level knowledge about obesity, 32.0% of respondents have mediumlevel knowledge about obesity, and 12.0% of respondents have a low-level knowledge about obesity. The greatest number of obesity cases occurs in the age group of 30-39 years, whichwere 15 people (30.0%). Most of housewives are graduated under elementary school, which is 50%. In addition, 56.0% of housewives do not have occupation. Respondents who have highest Waist Hip Circumference Ratio were 6 people (12.0%). Spearman Rank-analysis results showed there is no correlation between housewives’ knowledge about obesity and their waist hip ratio, with a value of r = - 0.746 and p = 0.000. To sum up, the higher the knowledge level is the lower their waist hip ratio is.Keywords: knowledge of obesity and waist hip ratio